Pemberdayaan Masyarakat Desa Wisata Pada Masa Pandemi Covid-19 - Latianingsih, Nining; Winarni Susyanti, Dewi; Syarweni, Narulita; L. Rudatin, Christina (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2021)
This community service is the result of research from the 2020 implementation team entitled the response to policies during the COVID-19 pandemic and considerations for formulating tourism village management policies in the future. This community empowerment program in the tourist village of Cisarua sub-district, Bogor district, is a PNJ tourism village. The scheme implemented in this community service is PNJ Higher Education Excellence Community Service. The outbreak of the COVID-19 virus has made various lines of life experience difficulties, especially economic problems. Those who are affected are the Tourism Village community in Cilember Village, especially MSMEs. In addition to the pandemic, they also experienced a decrease in turnover and lack of marketing. Therefore, the Community Service Team tries to provide solutions to these obstacles that have to do with community development and empowerment. The solution given is how to empower the community through online-based product implementation activities and digitalization-based marketing as well as providing supporting tools for activities and facilitating production activities as well as related to the development of tourist villages. The next program after being given training is mentoring so that the funds run well. The outputs of this activity are in addition to journal articles, there are seminar articles, activity videos, books and intellectual property rights. For the sustainability of this community empowerment, it is hoped that the community will be able to operationalize and develop business programs through online so that the tourism village community is economically independent. Pengabdian kepada masyrakat ini adalah merupaka hasil penelitian dari tim pelaksanaan tahun 2020 yang berjudul respon terhadap kebijakaan pada saat pandemic covid 19 serta pertimbangan perumusan kebijakan pengelolaan desa wisata dimasa depan. Program pemberdayaan masyarakat di desa wisata kecamatan Cisarua kabupaten Bogor ini merupakan binaan desa wisata PNJ. Skema yang dilaksanakan dalam pengabdian masyarakat ini adalah Pengabdian kepada Masyarakat Unggulan Perguruan Tinggi PNJ. Mewabahnya virus covid 19 ini telah membuat beragam lini kehidupan mengalami kesulitan terutamah masalah perekonomian. Yang termasuk kena imbas adalah masyarakat Desa Wisata yang ada di Desa Cilember khususnya UMKM. Selain pandemic juga mereka mengalami penurunan omzet serta kurangnya pemasaran . oleh karena itu tim Pennngabdi kepada masyarakat mencoba memberikan solusi terhadap kendala ini yang ada hubungannya dengan pengembangan serta pemberdayaan masyarakat. Solusi yang diberikan adalah bagaimana cara untuk memberdayakan masyarakat melalui kegiatan implementasi produk berbasis online serta pemasaran berbasis digitalisasi serta memberikan alat penunjang untuk kegiatan serta mempermudah dalam kegiatan produksi serta berkaitan dengan pengembangan desa wisata. Program selanjutnya setelah diberikan pelatihan adalah pencampingan agar berkelanjutan dana berjalan dengan baik. Luaran kegiatan ini adalah selain artikel jurnal adalah artike seminar, video kegiatan, buku serta HKI. Untuk keberlajutan pemberdayaan masyarakat ini diharapkan masyarakat mampu mengoperasionalkan serta mengembangkan proram usaha melalui online sehinggan secara ekonomi masyarakat desa wisata ini menuju mandari.